GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG PEMBERIAN MPASI PADA BAYI USIA 6-12 BULAN: GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG PEMBERIAN MPASI PADA BAYI USIA 6-12 BULAN - Heni Safitria; Mulyaningsih (Universitas Duta Bangsa Surakarta, 2023)
Background: MPASI is a food introdued to infants at 6 months of age to meet their nutritional needs. According to Indonesia hralth demography surveys beby who reeive 0-1 months 9,6%, at 2-3 months at 16,7%, and 4-5 months at 43,9%. Objective : Find out the level of mother’s knowledge about giving weaning food to baby aged 6-12 months. Methods: Descritive research. The sampling technique with total sampling of 37 mothers in Pengkol village. Results: The results of the univariate show the respondents characteriate as folloe some mothers had graduated in hight school (62,2%), aged 20-35 years (81,1%), woeked as housewife (62,2%), and the level of mother’s knowledge in medium category (78,4%). Conclusion : The research showed that the level of mother’s knowledge about giving weaning food to beby is medium (78,4%)